A post-neoliberal era in Latin America? : revisiting cultural paradigms - Nehring, Daniel; Gómez Michel, Gerardo, 1969-; López, Magdalena (Policy Press scholarship online., 2019)
This book explores neoliberalism in contemporary Latin America as a set of interrelated cultural forms, offering a transnational and comparative perspective on the ways in which neoliberalism has transformed public discourses of self and social relationships, popular cultures and modes of everyday experience.